LIABILITY OF THESE WHO HAVE NOT BEEN BROUGHT UP UNDER THE CRIMINAL LAW OF THE REPUBLIC OF UZBEKISTAN (Scientific journal of the Fergana State University, 2023)
The main objective of each state is to safeguard the rights of minors. This article highlights the criminal penalties imposed on minors in the Republic of Uzbekistan, their peculiarities and the further liberalization of criminal penalties for minors.